Kind of Black : the musicians' labour market in Italy - Alessandro Balestrino (Center for Economic Studies and ifo Institute (CESifo), 2009)
It is estimated that only 5% of musicians in Italy are regularly employed. In an attempt at understanding such a peculiar situation, we build a theoretical model of the musicians' labour market in which we embed the main institutional features of the Italian system. We notice how the presence of taxation incentivates the formation of a black market for musicians and discourages talented agents from becoming full-time musicians in all second-best economies. In Italy both tendencies are particularly strong, and further exacerbated by the presence of an actuarially unfair pension system for musicians. These inefficiencies might be corrected by a two-fold policy: the reform of the pension system, and the introduction of a sufficiently large unemployment benefit for musicians. We notice that the first step, while highly desirable, is unlikely to be politically feasible in the current Italian institutional setting. The second step, which has a general interest for any second-best economy, is instead viable under certain circumstances.
Keywords: J44; Z11; 330; musician; labour market; moonlighting; unemployment benefit; Italy; Künstlerische Berufe; Arbeitsmarkt; Schwarzarbeit; Alterssicherung; Arbeitslosenversicherung; Steuerwirkung; Italien